2021
DOI: 10.1038/s42003-021-02042-z
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin delays ovarian aging in mice by slowing down the exhaustion of ovarian reserve

Abstract: Studies have shown that melatonin (MLT) can delay ovarian aging, but the mechanism has not been fully elucidated. Here we show that granulosa cells isolated from mice follicles can synthesize MLT; the addition of MLT in ovary culture system inhibited follicle activation and growth; In vivo experiments indicated that injections of MLT to mice during the follicle activation phase can reduce the number of activated follicles by inhibiting the PI3K-AKT-FOXO3 pathway; during the early follicle growth phase, MLT adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 72 publications
0
12
0
1
Order By: Relevance
“…Recent studies have accentuated the importance of MLT in multiple biological processes, specifically in regulating circadian rhythms, hormone endocrine, neuroimmunological and reproductive processes [ 26 , 27 , 28 , 29 ]. Additionally, MLT can modulate cell proliferation, differentiation and apoptosis by sequential activation of multiple signaling molecules [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have accentuated the importance of MLT in multiple biological processes, specifically in regulating circadian rhythms, hormone endocrine, neuroimmunological and reproductive processes [ 26 , 27 , 28 , 29 ]. Additionally, MLT can modulate cell proliferation, differentiation and apoptosis by sequential activation of multiple signaling molecules [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al found that co-treatment with the antioxidant melatonin prevented cisplatin-induced disruption of the follicle reserve, preserving the number of primordial follicles in the ovary, which quantified the various stages of growing follicles, including primordial, primary, secondary, and antral [ 47 ]. Yang et al have shown that administration of melatonin to postnatal mice during the follicle activation phase and the early follicle growth phase, can reduce the number of activated follicles and suppress follicle growth and atresia, respectively [ 48 ]. Tamura et al found that old mice treated with melatonin had significantly more primordial, primary, secondary and antral follicles than the old controls [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, another antioxidant, is synthesized in the human body naturally. Melatonin regulated against mitochondrial oxidative damage and therefore ameliorated oocyte aging and ovarian reserve exhaustion in mice [ 108 , 120 , 121 , 122 , 123 , 124 ]. Tafenoquine (TFQ), an FDA-approved antimalarial drug, is applied to treat Trypanosoma brucei infection by targeting ROS and electron transport complex III [ 125 , 126 ].…”
Section: Potential Therapeuticsmentioning
confidence: 99%
“…There is no drug reported to increase the FOXO3 level. While a recent study mentioned that melatonin administration inhibited FOXO3 from nuclear transitions [ 124 ]. Moreover, FOXO3 is the major target of Akt and can be inactivated by Akt.…”
Section: Potential Therapeuticsmentioning
confidence: 99%